Implementation of zero burning technique among smallholder in Kuala Medang, Pahang / Nur Afiqah Md Said - Md Said, Nur Afiqah (Faculty of Plantation and Agrotechnology, 2019)
The production of oil palm takes more than a quarter of global consumption as oil crop and provides. However, there are concerns about how the development of oil palm industries will affect the environment particularly the deforestation and replanting in Malaysia. The problem arises as producers choose to do open burning method in deforestation and replanting oil palm. In order to cope with the problem, the burn method has been replaced with the no burn method, which is both environmentally friendly and economically superior to the burn method. The zero burning technique has been include as one of the condition of Malaysia Sustainable Palm Oil Certificate. This study aim to examine the level of knowledge, interest and effort of the smallholder on implementing zero burning technique. Furthermore, this study is done in encouraging smallholder on how zero burning technique can give benefits to the environment and oil palm plantation. Survey was conducted by using the simple random sampling method and distributed among 118 smallholders at Kuala Medang, Pahang. The data was analysed by using the software Statistical Package for Social Science (SPSS). Then, the data summarized and gather based on the parameters of the method of measuring data. The data was being analyse in term of factor analysis, descriptive analysis, correlation testing and multiple regression analysis. From this study, it is found that all factors knowledge, interest and effort have positive correlation with implementation of zero burning technique. All of these factors are very important in influencing implementation of zero burning at oil palm plantation.